Nieznany wiersz Adama Mickiewicza? Rękopis tekstów poetyckich z pierwszej połowy XIX wieku w Bibliotece Poznańskiego Towarzystwa Przyjaciół Nauk. Komunikat - Pietrowicz, Joanna (Poznańskie Studia Polonistyczne. Seria Literacka, 2010)
The Library of the Poznań Society of Friends of Arts and Sciences has been recently enriched by the accession of the manuscript “Poetical texts from the first half of the nineteenth century”. The manuscript includes a number of patriotic poems put down in the manuscript between 1848-1849. The article provides information on the physical description of the manuscript item (its present shelf number being: rkp. 2112) and a detailed list of its contents. Individual works have been listed in alphabetical order according to the names of the authors, with annotations concerning first editions. The bulk of the poems included in the manuscript were published prior to their inclusion in the manuscript, some of them after the year 1849. At the present stage of the investigation, some of the poems have not been confirmed to have been published earlier. An anonumous 12-verse poem without a title, attached to the communique at full length, has been identified by the author of the article as a poem whose last four verses were published in 1881 in the book Kraków — Zagrzebiowi under the title W albumie księcia Golicyna by Adam Mickiewicz. The article is intended to stimulate those engaged in research of the history of literature in further investigations concerning the said collection of poems, in particular the last mentioned text.